2022
DOI: 10.3390/separations9080227
|View full text |Cite
|
Sign up to set email alerts
|

Research into Gas Chromatography–Mass Spectrometry (GC-MS) for Ensuring the Effect of 1 MeV-Accelerated Electrons on Volatile Organic Compounds in Turkey Meat

Abstract: One of the most important tasks in the food industry is the search for alternative biochemical markers of radiation treatment in dietary, chilled meat products such as chicken and turkey. Major organic volatile chemicals found in meat products can be precisely identified using gas chromatography coupled with mass spectrometry. In the response to the needs of the food industry, our research team conducted a series of experiments involving the irradiation of chilled poultry meat using an electron accelerator. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
3
4
0
1
Order By: Relevance
“…The primary and aromatic alcohols increased with treatment up to 2.0 kGy or 4.0 kGy, then at higher doses decreased slightly in both matrices (Figures 2a and 3a,b). These compounds are the by-products of the primary oxidation of unsaturated fatty acids, and their decreased amount with higher doses is probably due to the further oxidation to aldehydes, as reported by Bliznyuk et al [18]. The Brie secondary alcohols showed a linear behavior in the irradiated samples (Figure 2b), while in the Camembert, the trend was in line with this of the primary alcohols.…”
Section: Voc Identification and Characterizationsupporting
confidence: 78%
See 1 more Smart Citation
“…The primary and aromatic alcohols increased with treatment up to 2.0 kGy or 4.0 kGy, then at higher doses decreased slightly in both matrices (Figures 2a and 3a,b). These compounds are the by-products of the primary oxidation of unsaturated fatty acids, and their decreased amount with higher doses is probably due to the further oxidation to aldehydes, as reported by Bliznyuk et al [18]. The Brie secondary alcohols showed a linear behavior in the irradiated samples (Figure 2b), while in the Camembert, the trend was in line with this of the primary alcohols.…”
Section: Voc Identification and Characterizationsupporting
confidence: 78%
“…Among these radiation-induced chemical changes, there is the production of volatile organic compounds (VOCs), which is dependent on both the dose level and on the presence of O 2 [14][15][16]. Hence, specific VOCs, such as hydrocarbons, aldehydes, ketones, esters, alcohols and sulfur-containing compounds, could be potential markers for several foodstuffs such as meats [16][17][18], fish [19][20][21] and fruits [22,23]. To date, detailed studies in dairy products on VOC behavior as a result of the irradiation treatment and dose level are still lacking [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the dose–effect relationship of VOC concentration was nonlinear, which, as our mathematical model shows, can result from two competing processes: the decomposition and accumulation of VOCs after irradiation as a result of the decomposition of other VOCs and biomacromolecules, such as fatty acids, proteins and carbohydrates. According to the model developed and published by our team [ 33 ], a volatile compound A present in the food sample at concentration C A is caused by the ionizing radiation to decompose at a rate k A , which is the number of compounds A decomposed per unit of absorbed dose (Gy −1 ). Under irradiation, compound A can transform into other volatile organic compounds of different fractions, depending on the type of the resulting compound.…”
Section: Resultsmentioning
confidence: 99%
“…На основе анализа поведения концентраций ЛОС в образцах говядины, индейки, семги и картофеля, облученных в дозах 0,1-10 кГр и на основе модельных экспериментов, проведенных со стандартными образцами летучих органических соединений в физиологическом растворе, был предложен механизм изменения содержания ЛОС в образцах продукта после воздействия излучения, основанный на конкурирующих процессах радиационно-индуцированного распада ЛОС и накопления ЛОС за счет распада других органических молекул [4], а также предложена функция, описывающая изменение концентрации идентифицированных соединений от дозы облучения:…”
Section: актуальная биотехнология №1 2023unclassified